(untitled) (Perner’s Contacts, 2013)
Load securing by lashing straps is a common lashing method to secure a cargo by lashing. Lashing straps, usually made from polyester, are elastic lashing. For direct lashing methods some pretension is assumed and cargo movement can elongate lashings up to restraining force or up to lashing capacity of lashing straps. When top-over lashing is usually design, cargo movement is not taken into consideration but in longitudinal direction forwards this traditional approach gives too many lashing straps. Therefore if we take into consideration longitudinal movement of a cargo self-tensioning effect of top-over lashing increases the tension force in lashing during cargo movement. The highest the elongation and the length of lashing straps the highest cargo movements are expected. Based on measurement results of elongation of selected lashing straps expected cargo movements in longitudinal direction forwards can be evaluated.